Navigating the Role and Approach of Gut Microbiota in Addressing Alzheimer's Disease Pathogenesis - Imrana Jazuli; Akeela Jazeel; Lakshmi Selvaratnam; Deepa Alex; Yatinesh Kumari (Progress in Microbes and Molecular Biology)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by amyloid beta plaques and tau protein neurofibrillary tangles, leading to cognitive decline. The lack of effective treatments compounds the significant human and financial burdens AD poses. Despite extensive research, the exact mechanisms of the disease remain elusive. Recent studies have shown promise in using anti-Aβ antibodies to reduce amyloid accumulation and slow dementia progression. However, diversifying therapeutic strategies is crucial for making meaningful progress. In recent years, research has increasingly focused on the microbiota-gut-brain axis in AD. Mounting evidence suggests that changes in gut microbiota composition are linked to AD progression, implicating various pathways. Dysregulation of microbiota taxa can trigger systemic inflammation by increasing gut permeability, ultimately leading to neural damage and neurodegeneration. Poor dietary habits and aging exacerbate gut dysbiosis, worsening AD pathology. However, investigations in this area are still in their early stages, with many aspects awaiting exploration and understanding. A thorough comprehension of the complex interactions within the microbiota-AD relationship is essential for refining therapeutic approaches. Interventions targeting gut microbiota, such as dietary adjustments, probiotics, and faecal microbiota transplantation, offer potential as therapeutics. This review highlights the detrimental role of gut dysbiosis in AD, offering insights into enhancing therapeutic avenues for the disease.